Entre identidades diaspóricas: Tituba e Condé nas linhas da Ancestralidade - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
This dissertation analyzes Maryse Condé's work I, Tituba, Black Witch of Salem (2019), examining the construction of Tituba's diasporic identity and its connection to the author's literary and biographical trajectory. Furthermore, it explores the ancestrality and writing-living present in the character's reconfiguration, showing how writing can be an instrument of resistance against silencing and structural racism. For this study, we draw on an interdisciplinary theoretical framework that includes decolonial studies, Black feminism, cultural studies, and literary theory, drawing on authors such as Trouillot (2016), Bhabha (1998), Kilomba (2019), Ricoeur (1994), Said (2003), Evaristo (2020), hooks (2014, 2015, 2022), and Spivak (2010). The research begins with a study of Tituba's reconfiguration based on Trouillot (2016), highlighting how superficial representations reinforce stereotypes and render marginalized voices invisible, and with Ricoeur (1994), to examine her narrative constructions. It then analyzes the marginalization of women's writing through Woolf (2014) and Cixous (2022), addressing the intersection of race and gender in feminism through hooks (2015) and Kilomba (2019). Maryse Condé's life and work trajectory is explored with support from Meireles (2007), highlighting Bhabha's (1998) concepts of in-betweenness and diaspora in Fanon (1961, 2008) and Hall (2006). This research presents Evaristo's (2020) concept of writing-living, articulating it with Krenak's (2022) philosophy and hooks' (2022) concept of belonging. The narrative analysis focuses primarily on Tituba's identity construction and geographic and cultural exile, drawing on Said (2003) and Fanon (1961, 2008). It then discusses the character's double subalternization as outlined by Spivak (2010). Finally, it explores ancestrality with Evaristo (2020) and belonging with hooks (2022), highlighting how memory and ancestrality articulate to transcend barriers. Writing-living and belonging are investigated as fundamental elements for claiming spaces of representation and voice. The contribution of this research is to highlight the importance of ancestrality and writing-living in the construction of Black female identity, in addition to demonstrating how literature can serve as a tool of resistance and a means of fighting against oppression, thereby promoting the visibility and voice of Black women.
Keywords: Identidade diaspórica; Ancestralidade; Escrevivência; Tituba; Maryse Condé; Letras